(untitled) (Cardiovascular Journal, 2012)
Background: The CONTROL (COversyl in Newly diagnosed stage-II & unconTROlled hypertensivepatients triaL) was performed with an objective to evaluate the blood pressure (BP) lowering efficacyand tolerability of Perindopril 8mg in newly diagnosed stage II patients and uncontrolledhypertensive patients among Bangladeshi population. Methods: This was an open-label, observational, multi-center study conducted in consultationcenters for out-patients located in different cities of Bangladesh. Adults, aged above 18 years withnewly diagnosed stage-II hypertension or uncontrolled hypertension, were recruited. Patients weretreated with Perindopril 4mg daily for first 1 week, afterwards uptitrated to Perindopril 8 mg dailyand continued treatment for 12 weeks. Patients were followed-up at week-1, week-4, week-8 andweek-12. Results: In total, 245 patients were enrolled. Among them, 88 were newly diagnosed stage-II (Group-I) and 157 were uncontrolled (Group-II) hypertensive patients. Male and female distribution was57% and 43% respectively. Mean age of patients was 54.5 ±11.7 years.After 12 weeks treatment, there was a significant reduction in BP from baseline (p<0.001) in overallpopulation as well as in Group I and in Group II. In overall population, the mean BP reduction was-31/-15 mmHg (from 163.7/96.8 mmHg to 132.4/81.7 mmHg. In Group I, the reduction was -33/-16mmHg (from 166.5/98.2 mmHg to 133.4/82.0 mmHg) and in Group II, -30/-14 mmHg (from 159.3/95.6 mmHg to 129.1/81.6 mmHg).10 patients (4.1%) had to discontinue the treatment due to adverse effects. Dry cough (2%) andhypotension (1.2%) were the main cause of discontinuation. Perindopril 8mg was well tolerated asindicated by the high proportion of physicians (81%) reporting good to excellent tolerability atweek 12. Conclusion: This study suggests that Perindopril 8mg is effective and safe in the treatment ofhypertension in Bangladeshi patients. DOI: http://dx.doi.org/10.3329/cardio.v5i1.12272 Cardiovasc. j. 2012; 5(1): 44-50